2023
DOI: 10.1186/s13048-022-01085-y
|View full text |Cite
|
Sign up to set email alerts
|

Plasma metabolomic characterization of premature ovarian insufficiency

Abstract: Background Premature ovarian insufficiency (POI) patients are predisposed to metabolic disturbances, including in lipid metabolism and glucose metabolism, and metabolic disorders appear to be a prerequisite of the typical long-term complications of POI, such as cardiovascular diseases or osteoporosis. However, the metabolic changes underlying the development of POI and its subsequent complications are incompletely understood, and there are few studies characterizing the disturbed metabolome in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 57 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…Glycerophospholipids serve as the primary constituents of mammalian cell membranes, exerting a pivotal role in signal transduction, cellular proliferation, protein function, and other essential biological processes [ 57 , 67 , 68 ]. In line with these previous studies, we also observed an up-regulation of the glycerophospholipid metabolic pathway in women with DOR.…”
Section: Discussionmentioning
confidence: 99%
“…Glycerophospholipids serve as the primary constituents of mammalian cell membranes, exerting a pivotal role in signal transduction, cellular proliferation, protein function, and other essential biological processes [ 57 , 67 , 68 ]. In line with these previous studies, we also observed an up-regulation of the glycerophospholipid metabolic pathway in women with DOR.…”
Section: Discussionmentioning
confidence: 99%
“…The most abundant metabolites detected by LC-SACI-MS, following the fermentation process, were organic acids; in particular, formic acid (89.5 g L −1 ), butyric acid (7.45 g L −1 ) and butanedioic acid (3.58 g L −1 ). Organic acids are typical metabolites in dark fermentation processes as described by different authors [21,22]. Clostridium spp.…”
Section: Exhausted Broth Characterizationmentioning
confidence: 99%
“…Premature ovarian insufficiency (POI) is the condition of ovarian function decline leading to amenorrhea for over a year before 40 years of age ( 237 ), which may be associated with genetic, medical, immunological, environmental, and other factors. POI is associated with metabolic disturbances, including glucose and lipid metabolism, which may increase the risk of long-term complications, such as cardiovascular diseases and osteoporosis ( 238 ). Glucose metabolism is regulated by insulin.…”
Section: Abnormal Senescencementioning
confidence: 99%
“…Estrogen also affects lipid metabolism by regulating the expression and activity of enzymes and receptors involved in lipid synthesis, transport, and degradation ( 240 ). Zhou et al ( 238 ) found that patients with POI had higher levels of plasma glucose, insulin, Homeostatic Model Assessment for Insulin Resistance (HOMA-IR, a marker of insulin resistance), plasma triglycerides, total cholesterol, low-density lipoprotein cholesterol, and apolipoprotein B compared with healthy controls. Moreover, they identified several metabolites related to glucose metabolism and lipid metabolism that were altered in patients with POI, including lactate, pyruvate, citrate, carnitine, acylcarnitine, glycerol, and glycerophospholipids.…”
Section: Abnormal Senescencementioning
confidence: 99%